Los factores determinantes de la Competitividad utilizados por las empresas industriales de la provincia de San Martín, durante el año 2012 - Arrelucea Grández, Roxana (2013)
The problem of industrial enterprises in Peru has shown that despite having an effective administration, tend to continue to have problems reducing their development. Studies made such as CENTRUM, the Peruvian institute of Economics, CEPLAN, among others, assert the importance of knowing certain factors competitiveness, ensuring increased productivity, however by ignoring these factors which are also not very specific to the national reality and much less local. This research was based on studies related to competitiveness and the factors that compose it, stressing the most relevant, within a local context, specifically industrial enterprises in the Province of San Martín, in order to know, analyze. Identify and structure the influence they had in the time period in 2012, based on the tenets of Michael Porter. The research data were collected by applying a survey, made with certain criteria, thus when processed, was obtained as a result the determinants of competitiveness, which are training, certification and planning and when corresponding analysis determined that these were underdeveloped in conclusion it denotes an unfavorable influence on the development of industrial enterprises. Given the results and related information, was raised a structure based on the diamond model of competitiveness of Porter, which can be adapted to the reality independent of each company and to optimize its implementation and the recommendations provided in the order to support industrial enterprises in productive development, en route to competitiveness.